TECHNOLOGICAL STARTUPS IN INDIA: TRANSFORMATIVE FORCES SHAPING THE INDIAN ECONOMY - Dr. Pravin R. Choube (Ecomind Press, 2025)
Technological startups in India have gained significant momentum in recent years, serving as drivers of economic growth and innovation. The startup ecosystem has witnessed an extraordinary surge, particularly in the fields of fintech, e-commerce, artificial intelligence (AI), and healthtech. This paper analyzes the role of technological startups in transforming the Indian economy, with a focus on job creation, technological innovation, and economic development. By examining recent trends in the startup ecosystem, funding patterns, government policies, and their long-term economic impact, this research explores how these ventures have contributed to India's economic growth and their future potential. The study also highlights challenges faced by startups, such as regulatory barriers and funding gaps. The paper concludes that the startup ecosystem plays a crucial role in shaping India’s economic future, and with the right support, technological startups can lead India to become a global innovation hub.